Reconstructing the Legal Framework of AI Use in Indonesia's 2024 Presidential Campaign: A Progressive and Responsive Law Perspective - Tasya, Izzuma; Susmayanti, Riana; Al-Uyun, Dhia (IJBLE Scientific Publications Community Inc., 2025)
The rise of Artificial Intelligence (AI) in Indonesia's 2024 presidential campaign reveals a significant legal gap in Law No. 7 of 2017 on Elections. Using a normative juridical approach, this study examines the 1945 Constitution, Election Law, and Constitutional Court Decision No. 166/PUU-XXI/2023. Findings show that while the Court prohibits